Environmental interpretation evaluation in natural areas - Munro, J.; Morrison Saunders, A.; Hughes, Michael (Channel View Publications, 2008)
Environmental interpretation is widely assumed to influence visitor behaviour and reduce impacts on a natural site. Assumptions of cause and effect are difficult to attribute and relatively few studies evaluate the effects of interpretation on visitor behaviours. We reviewed a sample of the interpretation evaluation literature available through online databases. We looked at the internal validity of evaluative studies and compared different interpretive approaches in terms of outcomes. Findings indicate an evaluative emphasis on quantifying knowledge gain and attitude change with few studies extending to measurement of behavioural change. The large number of possible variables and small number of completed studies prevent substantive conclusions on the role of interpretation in promoting more sustainable visitor behaviour. Further research is needed in terms of robust evaluative studies to facilitate development of a clear understanding of interpretive programs' influence on visitor behaviour. It is problematic to assess environmental interpretation as a visitor management tool until further such evaluative studies are performed.